Blood utilization quality indicators in a tertiary care center in South India - Remi Remakanth (Global Journal of Transfusion Medicine, 2020)
Background: Injudicious over-ordering of blood components not only burdens the physical and human resources but also increases the cost of health care. Moreover, such practices have a greater implication in developing countries like ours where there is a scarcity of voluntary blood donors and insufficient blood supply to cater to increasing demands. Therefore, there is a need for continuous monitoring of the utilization of blood components and to audit the transfusion practices to identify areas of concern for blood usage. Ours is a 1600 bedded super specialty health center with 100% bed occupancy. The objective of the study was to analyze the trend of utilization of blood components and transfusion practices by various medical and surgical specialties by determining the blood utilization quality indicators at our center. Methods: This was a retrospective and cross-sectional study done over a period of 7 months from January 2018 to July 2018. The data for blood utilization quality indicators in the first half can be taken as the representative of the entire year. The data pertaining to the number of requisitions received as well as cross-matches done and issues made were collected from transfusion requisition forms, cross-match, and issue registers and analyzed. The parameters used in the analysis were crossmatch to transfusion ratio (CT ratio), transfusion index (TI), and transfusion probability (%T). Results: During the 7-months study period, a total of 28,317 transfusion requisitions were received and 34,701 blood components were issued. The total cross-matched red blood cell (RBC) units were 10,861 and the total RBC units transfused were 10,066. The overall C/T ratio was found to be 1.57. The transfusion probability (%T) and TI were calculated as 79% and 1.18, respectively, in our study. Conclusion: The CT ratio, transfusion probability, and TI demonstrated that there is an efficient blood utilization at our center. Regular auditing of blood transfusion services should be practiced at every hospital wherein the Maximum Surgical Blood Ordering Schedule can be modified and implemented progressively, following evidence-based blood transfusion guidelines.